1996
DOI: 10.1093/molehr/2.12.943
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and possible relevance of Y-linked microdeletions in babies born after intracytoplasmic sperm injection and their infertile fathers

Abstract: Microdeletions linked to deletion intervals 5 and 6 of the Y chromosome have been associated with male factor infertility. Members from at least two gene families lie in the region containing azoospermia factor (AZF), namely YRRM and DAZ. With the advent of intracytoplasmic sperm injection (ICSI), it is possible for men with severe male factor infertility to produce a child. The genetic consequences of such a procedure have been questioned. This report describes the first study of a population (32 couples) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(70 citation statements)
references
References 35 publications
2
65
0
3
Order By: Relevance
“…Until now only 17 male and 18 female ICSI babies born from fathers affected by Yq microdeletions have been reported (Kent-First et al 1996;Mulhall et al 1997;Jiang et al 1999;Kamischke et al 1999;Kleiman et al 1999;Cram et al 2000;van Golde et al 2001;Peterlin et al 2002;Oates et al 2002). It appears that the children are phenotypically normal, except for one son born with pulmonary atresia and a hypoplastic right ventricle (Page et al 1999) and no ambiguous genitalia or Turner syndrome have been observed among them.…”
Section: Genetic Counsellingmentioning
confidence: 99%
“…Until now only 17 male and 18 female ICSI babies born from fathers affected by Yq microdeletions have been reported (Kent-First et al 1996;Mulhall et al 1997;Jiang et al 1999;Kamischke et al 1999;Kleiman et al 1999;Cram et al 2000;van Golde et al 2001;Peterlin et al 2002;Oates et al 2002). It appears that the children are phenotypically normal, except for one son born with pulmonary atresia and a hypoplastic right ventricle (Page et al 1999) and no ambiguous genitalia or Turner syndrome have been observed among them.…”
Section: Genetic Counsellingmentioning
confidence: 99%
“…Sons of individuals with such a microdeletion would inherit the microdeletion and consequently may be infertile (26). Although a microdeletion of the Y chromosome is not thought to be associated with other health problems, few data exist on the phenotypes of the sons of fathers with such genetic abnormalities.…”
Section: Y-chromosome Microdeletionsmentioning
confidence: 99%
“…Sons of individuals with a Y-chromosome microdeletion will inherit the microdeletion and may consequently be infertile (18). Although a microdeletion of the Y chromosome is not thought to be associated with other health problems, few data exist on the phenotypes of the sons of fathers with such genetic abnormalities.…”
Section: Y-chromosome Microdeletionsmentioning
confidence: 99%